Decomposition of Intuitionistic Fuzzy Matrices. Issue 3 (1st September 2016) - Muthuraji, T.; Sriram, S.; Murugadas, P.
Abstract: In this paper, we study some properties of modal operators in intuitionistic fuzzy matrix and we introduce a new composition operator and discuss some of its algebraic properties. Finally, we obtain a decomposition of an intuitionistic fuzzy matrix by using the new composition operator and modal operators.